2011
DOI: 10.1002/pip.1233
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cu(In,Ga)Se2 thin‐film formation during the multi‐stage co‐evaporation process

Abstract: In order to transfer the potential for the high efficiencies seen for Cu(In,Ga)Se 2 (CIGSe) thin films from co-evaporation processes to cheaper large-scale deposition techniques, a more intricate understanding of the CIGSe growth process for high-quality material is required. Hence, the growth mechanism for chalcopyrite-type thin films when varying the Cu content during a multi-stage deposition process is studied. Break-off experiments help to understand the intermediate growth stages of the thin-film formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
85
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 64 publications
4
85
2
Order By: Relevance
“…39 At first, this seems to be in contradiction to our finding of a higher Na content at the surface of the Cu-rich compared to that of the Cu-poor CIGSe/Mo/PI samples. This discrepancy can be explained taking into account that according to Wei et al 20 the main effect of Na (present in small quantities) is the elimination of In Cu defects, which preferably form in Cu-poor CIGSe absorbers.…”
Section: B Xps and Xaes Detail Spectra Of Nacontrasting
confidence: 56%
See 1 more Smart Citation
“…39 At first, this seems to be in contradiction to our finding of a higher Na content at the surface of the Cu-rich compared to that of the Cu-poor CIGSe/Mo/PI samples. This discrepancy can be explained taking into account that according to Wei et al 20 the main effect of Na (present in small quantities) is the elimination of In Cu defects, which preferably form in Cu-poor CIGSe absorbers.…”
Section: B Xps and Xaes Detail Spectra Of Nacontrasting
confidence: 56%
“…Both series were intentionally deposited Cu-poor with respect to the standard Cu:(In þ Ga):Se ¼ 1:1:2 CIGSe stoichiometry, but the degree of Cu deficiency was varied by adjusting the duration of the third deposition stage. 39 It should be noted, however, that the nominal Cu/(In þ Ga) composition at the end of second deposition stage was approx. 1.15.…”
Section: Methodsmentioning
confidence: 99%
“…It is well known from the literature that an intermediate Cu-rich composition during co-evaporation of Cu(In, Ga)Se 2 absorber films is favorable for the formation of a large grained morphology and for high energy conversion efficiencies of resulting solar cells. 35,36 Also for co-evaporated CZTS it was shown that a Cu-rich growth has a positive effect on the formation of large grains. 13,15,37 In these cases, the Cu excess is subsequently removed by etching 13 or by a Cupoor co-evaporation stage 15 to obtain single phased CZTS.…”
Section: Growth Modelmentioning
confidence: 99%
“…[2][3][4] However, a Cu-rich stoichiometry is known to lead to the formation of a secondary phase, Cu 2-x Se (x ¼ 0-0.25), at the absorber surface and at grain boundaries (GBs) within the film. [5][6][7] The secondary phase formed at the surface can be removed by chemical treatments (NaCN, KCN, etc.)…”
mentioning
confidence: 99%